O léxico dos pescadores da comunidade Arauaia - TELES, Maria Antônia Corrêa (2024)
This work aims to promote a study on the language of fishermen from the Arauaia community, located in the municipality of Barcarena-PA, highlighting their linguistic variation, especially the lexicon. We sought an in-depth study of the characteristic aspects of speech, valuing cultural, social, economic and ethnic factors. Based on these elements, we seek to build an approach to the lexicon of these fishermen, focusing on language, reality, social disparities and contrasts in the forms of linguistic expression, seeking theoretical support in theories that study the specificities of language, such as Sociolinguistics, Dialectology, Lexicon, Linguistic Prejudice and Linguistic Variation, respectively. These theories share the same context, giving the fishermen's language the possibility of creating their own linguistic reality in a society in which language transformations are in constant processes of transformation. This study was carried out through field research that favored data collection so that we could understand with greater relevance the lexicon of these fishermen in focus here.